2013
DOI: 10.1177/0959353513487532
|View full text |Cite
|
Sign up to set email alerts
|

Efforts to maintain a ‘just great’ story: Lesbian parents’ talk about encounters with professionals in fertility clinics and maternal and child healthcare services

Abstract: After lesbian couples have decided to become parents, their family-making journey entails a wide range of encounters with professionals in fertility clinics and/or in maternal and child healthcare services. The article presents the results of an analysis of 96 lesbian mothers’ interview talk about such encounters. In their stories and accounts, the interviewees draw on two separate and contradictory interpretative repertoires, the ‘just great’ repertoire and the ‘heteronormative issues’ repertoire. Throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 37 publications
3
56
0
1
Order By: Relevance
“…Participants' satisfaction with RHC can be seen as an indication of high-quality medical care and also some level of LGBTQ competent care, implying a certain acceptance of LGBTQ parents in Sweden. Similar to previous studies on same-sex mothers (31), the current study found that participants had mixed feelings regarding being satisfied despite lacking support. Our results indicated that it might be difficult for LGBTQ parents to tell their story about heteronormativity.…”
Section: Satisfaction With Rhc Despite Heteronormativitysupporting
confidence: 86%
“…Participants' satisfaction with RHC can be seen as an indication of high-quality medical care and also some level of LGBTQ competent care, implying a certain acceptance of LGBTQ parents in Sweden. Similar to previous studies on same-sex mothers (31), the current study found that participants had mixed feelings regarding being satisfied despite lacking support. Our results indicated that it might be difficult for LGBTQ parents to tell their story about heteronormativity.…”
Section: Satisfaction With Rhc Despite Heteronormativitysupporting
confidence: 86%
“…This heteronormative view, where everyone is expected to be heterosexual (Connell & Pearse, ), seems to be especially prominent in child healthcare. Previous research has reported that two‐mother families often are met by heteronormative language (Andersen et al, ; Crouch et al, ; Erlandsson et al, ; Malmquist & Zetterqvist Nelson, ; O’Niell et al, ; Röndahl et al, ; Wojnar & Katzenmayer, ). In this study, some nonbirth mothers were called partners, but most nonbirth mothers in our study did not want to be called partners, as they were mothers too.…”
Section: Discussionmentioning
confidence: 99%
“…Both international and Swedish studies have shown that two‐mother families experience heteronormativity and stigma in their encounters with healthcare professionals (Andersen, Moberg, & Bengtsson Tops, ; Crouch, McNair, & Waters, ; Erlandsson, Linder, & Häggström‐Nordin, ; Malmquist & Zetterqvist Nelson, ; O’Niell, Hamer, & Dixon, ; Röndahl, Bruhner, & Lindhe, ; Wojnar & Katzenmayer, ). Despite the experienced heteronormativity, Swedish research show a satisfaction in same‐sex mothers relationship quality, few symptoms of anxiety and depression, and low levels of parental stress compared to heterosexual couples (Borneskog, Lampic, Sydsjö, Bladh, & Skoog Svanberg, ; Borneskog, Sydsjö, Lampic, Bladh, & Skoog Svanberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this statement emphasizes that the definitions of family should be inclusive of all family formations and that health education programs should incorporate LGBT health issues to create a safe and non-judgmental space for SMW in healthcare settings. Despite these endorsements, SMW continue to experience stigma and discrimination in clinical settings (Malmquist and Nelson 2013) and have unmet medical needs (Everett and Mollborn 2014). …”
Section: Discussionmentioning
confidence: 99%